Effect of Maturity Stages on Potantial Nutritive Value of Rheum ribes L. - Kurt, Özer (My University, 2022)
The purpose of the current work was to designate the effect of maturity stages potential nutritive value, the chemical composition, condensed tannin (CT), gas production (GP), methane production, metabolizable energy (ME), and organic matter digestibility (OMD) of Rheum ribes L. Maturity stages significantly affected (P<0.05) the chemical composition, CT, GP, methane production, ME and OMD of Rheum ribes L. Dry matter (DM), crude ash (CA), crude protein (CP), ether extract (EE), CT, neutral detergent fiber (NDF) and acid detergent fiber (ADF) of Rheum ribes L. ranged from 92.73- 98.64%, 6.11-14.15%, 8.81-19.12%, 1.94-3.04%, 10.47-14.72%, 36.99-53.98% and 24.88-37.63% respectively. Gas production and methane production of Rheum ribes L. at 24 ranged from 29.73-40.60 ml and 2.63-5.50 ml respectively. ME and OMD of Rheum ribes L. ranged from 6.97-9.87 MJ kg-1 KM and 45.68-60.02% respectively. To sum up, maturity stages is a significant point on the nutritive value of Rheum ribes L. Nutritive value especially CP, ME and OMD of Rheum ribes L. decreased with advancing maturity. GP, ME and OMD were significant and negatively correlated with ADF and NDF contents, whereas positively correlated with CP. Moreover in vivo studies are needed to determine the effect of Rheum ribes L. on the feed intake and performance of ruminant animals.